2006
DOI: 10.1063/1.2210930
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring and electro-optical dynamics of thin liquid crystalline films in a polyimide cell: Experiment and theory

Abstract: The surface-dependent anchoring and electro-optical (EO) dynamics of thin liquid crystalline films have been examined using Fourier transform infrared spectroscopy. A simple nematic liquid crystal, 4-n-pentyl-4'-cyanobiphenyl (5CB), is confined as 40, 50, and 390 nm thick films in nanocavities defined by gold interdigitated electrode arrays (IDEAs) patterned on polyimide-coated zinc selenide (ZnSe) substrates [Noble et al., J. Am. Chem. Soc. 124, 15020 (2002)]. New strategies for controlling the anchoring inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…The softening of the elastic constants at higher temperatures leads to predictably faster electric-field-induced orientation rates; the relaxation rates, however, do not vary markedly with temperature. These striking experimental results are interpreted and accounted for semiquantitatively using a theoretical framework presented in our previous report …”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The softening of the elastic constants at higher temperatures leads to predictably faster electric-field-induced orientation rates; the relaxation rates, however, do not vary markedly with temperature. These striking experimental results are interpreted and accounted for semiquantitatively using a theoretical framework presented in our previous report …”
Section: Introductionmentioning
confidence: 85%
“…The liquid crystal EO cell employed and its means of fabrication have been described in detail in earlier reports. , The cell used in this study adopts the same design rules as described there. The ZnSe windows were polished to produce a nanometer-scale, grooved morphology that serves to align the LC director.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These previous studies have shown the nitrile group serves as an excellent indicator of the molecular orientation within the applied field. Lee et al showed a 180° change in field direction could be probed with the nitrile peak intensity as it changed along with molecular alignment in the field. , …”
Section: Introductionmentioning
confidence: 99%